2000
DOI: 10.1029/2000jc900083
|View full text |Cite
|
Sign up to set email alerts
|

Integrated use of altimeter and in situ data for understanding the water exchanges between the Tyrrhenian and Ligurian Seas

Abstract: Abstract. In this paper we examine the relationship between the seasonal and interannual variability observed in the water flow through the Corsica Channel and the sea level difference between the Tyrrhenian and Ligurian Seas. The steric contribution to the sea level difference, computed from historical hydrological data, is in good agreement with the stable presence of the seasonal signal in the water exchanges. We obtain the maximum steric difference in winter (-16 cm) and the minimum in summer (-2 cm). Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…Dynamical interpretation of the differences requires knowledge of whether these are due to a deeper baroclinic variability and/or a barotropic contribution. As shown by Vignudelli et al (2000), the steric contribution resulting from density variation in the upper layers is much larger than that due to the deep layers. By contrast, large-scale features, like the Bonifacio Gyre, clearly may extend beyond the 300 m depth, causing mass redistribution (bottom pressure variability), whose effect is to offset the total sea level.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Dynamical interpretation of the differences requires knowledge of whether these are due to a deeper baroclinic variability and/or a barotropic contribution. As shown by Vignudelli et al (2000), the steric contribution resulting from density variation in the upper layers is much larger than that due to the deep layers. By contrast, large-scale features, like the Bonifacio Gyre, clearly may extend beyond the 300 m depth, causing mass redistribution (bottom pressure variability), whose effect is to offset the total sea level.…”
Section: Discussionmentioning
confidence: 83%
“…The accuracy for the time-varying part of the single measurement is certainly better than this value, since the timeinvariant systematic error component is removed. Moreover, Vignudelli et al (2000), using measurements from a bottom pressure recorder deployed at Capraia Island, found that altimeter data matched the in situ data within 2.8 cm RMS after application of a 30-day half-amplitude Gaussian filter. This error value is not significantly greater than the 2-cm solution obtained near Sao Tome Island (Verstraete and Park, 1995) and indicates that the T/P-derived altimetric heights are accurate enough in the area when used to investigate the seasonal variability.…”
Section: Altimetric Heightsmentioning
confidence: 99%
See 3 more Smart Citations